Wild Edible Plants of Southern Part of Nevsehir in Turkey - ŞENKARDEŞ, İSMAİL (MARMARA UNIV, FAC PHARMACY, 2015)
The aim of this study is to represent the wild edible plants of southern part of Nevsehir (Acigol, Derinkuyu, Gulsehir, Nevsehir-Central District and Urgup) where is situated at the center of the region as named Cappadocia in Turkey. This study which is a part of a comprehensive ethnobotanical research, was carried out in the 98 settlement centers (including 81 villages) of the southern part of Nevsehir. Three excursions were made in several periods between June 2012-March 2014 lasting for 61 days in total. The information about local names, used part(s) and usages of the plants, was obtained from the native people living in the research area by personal interviews. The plant specimens which are the materials of this study, are kept in the Herbarium of the Faculty of Pharmacy, Marmara University (MARE). According to the results of this ethnobotanical study, total 165 taxa used for various purposes, were determined and 71 taxa (belong to 19 families) of which were utilized as wild edible plants in Nevsehir. The usages of these plants were recorded as: food stuff (59 taxa), herbal tea (14 taxa) and spice (3 taxa). All of the 71 taxa utilized as wild edible plants in Nevsehir and 3 taxa (Brassica deflexa, Cerasus incana var. velutina, Silene subconica) of them in Turkey, were recorded for the first time. Consequently, there is an important role of the plants on nutrition of the local people especially in spring time.
Keywords: Ethnobotany; Wild edible plants; Nevsehir; Turkey